2023
DOI: 10.1111/eci.14001
|View full text |Cite
|
Sign up to set email alerts
|

Sauna bathing, renal function and chronic kidney disease: Cross‐sectional and longitudinal findings from the KIHD study

Abstract: Background: It is uncertain if passive heat therapies are associated with adverse renal outcomes. We sought to evaluate the cross-sectional and longitudinal associations of the frequency of sauna bathing with renal function measures and chronic kidney disease (CKD). Materials and Methods:Baseline self-reported sauna bathing habits were assessed in 2071 men aged 42-61 years with normal kidney function. Baseline estimated glomerular filtration rate (GFR) and serum levels of creatinine, potassium (K) and sodium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Finnish sauna - In 2,071 middle-aged and older men aged 42–61 years with normal kidney function who were recruited into the KIHD prospective study, cross-sectional and longitudinal analysis showed that frequent sauna bathing (4–7 sauna sessions per week) was not associated with impaired renal function (as measured using estimated glomerular filtration rate and serum levels of creatinine, potassium and sodium) or the future risk of chronic kidney disease [ 59 ] ( Figure 2 ). Although intensive sweating, induced by sauna with dry or wet heat, usually increases losses of water, urea, sodium, potassium, and chloride, a sauna bath session does not cause significant longer-term changes in serum electrolyte or creatinine levels.…”
Section: Health Benefits Of Passive Heat Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finnish sauna - In 2,071 middle-aged and older men aged 42–61 years with normal kidney function who were recruited into the KIHD prospective study, cross-sectional and longitudinal analysis showed that frequent sauna bathing (4–7 sauna sessions per week) was not associated with impaired renal function (as measured using estimated glomerular filtration rate and serum levels of creatinine, potassium and sodium) or the future risk of chronic kidney disease [ 59 ] ( Figure 2 ). Although intensive sweating, induced by sauna with dry or wet heat, usually increases losses of water, urea, sodium, potassium, and chloride, a sauna bath session does not cause significant longer-term changes in serum electrolyte or creatinine levels.…”
Section: Health Benefits Of Passive Heat Therapiesmentioning
confidence: 99%
“…Model 3: Model 2 plus estimated glomerular filtration rate. Reproduced from Kunutsor SK, et al [ 59 ]. …”
Section: Health Benefits Of Passive Heat Therapiesmentioning
confidence: 99%